PENGARUH RELIGIUSITAS DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV CORIEN CENTRE MUARA BUNGO - Rivano Putra; Addiarrahman Addiarrahman; Khusnul Istiqomah (CV. Aksara Global Akademia, 2023)
In a company or organization basically aims to maximize profits, and to be able to achieve these benefits employees must be able to carry out work tasks optimally both in goods and services companies, so that the end result of the income earned will be more profitable and can cover expenses. Work really requires good individual skills to be able to carry out the job well. Islam regulates all aspects of human life, especially in terms of work, because work is an obligation that must be carried out by humans to fulfill their needs. Employee performance has a big influence on the development of the company. If the company has quality resources, it will create good performance and be able to develop to achieve goals. Factors that can affect employee performance are religiosity and job satisfaction. The purpose of this research is to find out whether religiosity and performance satisfaction affect the performance of CV Corien Center employees. The number of samples in this study was 30 people and used a saturated sampling technique where all members of the population were used as samples. Multiple regression analysis was used as a data analysis technique. The results showed that there was no influence between religiosity and job satisfaction on employee performance. The percentage of contribution is 10.6% and the remaining 89.4% is influenced by other variables outside of this study.